Depth of Water-Substrate Interface in Floating Culture and Nutrient-Enriched Substrate Effects on Green Apple Eggplant - Karla Kasihta Jaya; Benyamin Lakitan; Zaidan Panji Negara (AGRIVITA, Journal of Agricultural Science, 2019)
A successful development of low cost floating culture system (FCS) has opened an opportunity for local farmers to cultivate vegetables during prolonged flooding at riparian wetlands. Research was aimed to identify the optimal depth of water-substrate interface (WSI) and optimal rate of NPK fertilizer application (RFA) in cultivating green apple eggplant using the FCS. Depths of WSI were adjusted to 0, 1, 3, and 6 cm and substrate was enriched with 8.4, 12.6, and 16.8 g NPK per pot. The enriched substrates were contained in pots and placed on floating rafts with variable WSI depths. Experiment was arranged in Split Plot Design. WSI was assigned as main plot and RFA was as subplot. The results exhibited that direct contact between water surface and substrate significantly increased water moisture content, enhanced shoot growth, and increased fruit yield, regardless the WSI depths. However, WSI treatments decreased SPAD value and restricted root elongation when WSI depth was more than 3 cm. The RFA treatments up to 16.8 g per pot could enhance shoot and root growth, and increased the fruit yield. This yield increase was associated with the increasing number of fruits, not the fruit size.